Analisis Software Requirement Pada Klinik - Nazihah, Fasya; Widyarto , Setyawan (Proceedings of the Informatics Conference, 2026)
Clinics are one of the front lines of primary-level services in healthcare facilities. Health is very important for human life. In this modern era, changes in lifestyle have also transformed the clinic registration system, making it easier than before. However, the queue system is still not very effective in reducing waiting times, which can affect patients’ conditions, especially elderly people or patients who are ill. Therefore, it is important to manage waiting time properly so that patients feel comfortable with the services they receive. This application makes it easier for patients to register for doctor appointments online, so patients no longer need to queue directly at the clinic. Patients can also view their medical records and invoices through this application. This application was designed and developed to improve efficiency, effectiveness, professionalism, performance, as well as clinic access and services, particularly in terms of improving operational efficiency, enhancing patient services, better financial management, and performance monitoring. In using this application, there are three types of users: super administrator, administrator, and user.